Medical Plants Phytonyms of the Extreme North with the Component “ot” (Grass): Semantics and Word Formation - Malysheva, Ninel Vasilyevna; Chirikova, Nadezhda Konstantinovna; Vasilyeva, Alina Petrovna (Journal of History Culture and Art Research, 2019)
The article discusses the issues of the methods and principles of the formation of two-component names of medicinal plants (phytonyms) with the component “ot” (grass) growing on the territory of the Extreme North of Russia - Yakutia as part of an interdisciplinary research at the junction of linguistics and biology. Attention is paid to the study of semantic features of phytonyms of the Yakut medical plants. The results of linguistic analysis are presented, which are compared with the methods of using medicinal plants with herbal extracts and herbalists and collected during expeditionary work. Particular attention is paid to the definition of universal models of formation of medical phytonyms in the Yakut language and identifying some methods of the word-formation system of lexical units denoting names of medicinal plants based on the appearance and form of any of the parts, designating a characteristic place of growth, identifying a functional trait and determining the affiliation of a medicinal plant. The novelty of the research is seen in the fact that the study of the names of medicinal plants in the Yakut language is conducted for the first time. The relevance of the study is due to the fact that the study of the vocabulary of the Yakut language in a comparative historical aspect will improve the existing results and open new directions in the study of the history of the Turkic languages. Universal models of the formation of phytonyms of medicinal plants in the Yakut language are proposed, which reveal a regional peculiarity.